The method for termination of mid-trimester pregnancy with placenta previa: A case study. Issue 31 (5th August 2022) - Long, Qingyun; Wu, Shiyao; Du, Shuguo; Li, Ruyan; Zhao, Yun; Tang, Fei
Abstract : Background: Prenatal bleeding is very dangerous for pregnant women with placenta previa during termination of pregnancy in the mid-trimester. Traditionally, cesarean section or hysterectomy is used to stop bleeding. This study aims to investigate the method for termination of mid-trimester pregnancy with placenta previa, especially emergency uterine artery embolization (UAE) combined with cervical double balloon (CDB). Methods: A retrospective study was conducted based on 261 cases of mid-pregnancy termination in our hospital, where 34 cases with placenta previa were set as the observation group, and the remaining 227 cases were set as control group. At first, the termination method of Mifepristone combined with Misoprostol/Ethacridine Lactate was adopted. If the volume of prenatal bleeding was up to 400 mL, emergency uterine artery embolization (UAE) was implemented to stop bleeding, then cervical double balloon (CDB) was used to promote cervical ripening. Receiver operating characteristic (ROC) curves analysis was performed to assess the accuracy in predicting the length of placental edge crossed the cervical os for prenatal bleeding. Results: The number of gravidity/parities, the rate of cesarean section, the medical cost, the rate of previous cesarean section were all higher in the observation group than in the control group ( P < .05). The volume of prenatal hemorrhage, postpartum hemorrhage, the rate of puerperal morbidity, emergency UAE rate and ICU rate were higher in the observation group than in the control group ( P < .05). There were 4 cases showing prenatal hemorrhage up to 400 mL and undergoing emergency UAE + CDB in the observation group, while there were no such cases in the control group ( P < .05). An optimal cut-off value of 1.7cm for the length of placental edge crossed the cervical os in diagnosing prenatal hemorrhage demonstrated sensitivity and specificity of 75.0% and 86.7%, respectively (area under the ROC curve, 0.858). Conclusion: The combined therapy of mifepristone and Misoprostol/Ethacridine Lactate was useful for termination of mid-trimester pregnancy with placenta previa, and attention needs to be attached to prenatal hemorrhage during labor induction. Emergency UAE + CDB is a good combination method to treat prenatal hemorrhage and promote cervical ripening during the induction.